Altering screenwriting frameworks through practice-based research: a methodological approach. Issue 3 (2nd July 2020) - Dean, Levi
ABSTRACT: The aim of this paper is to propose a methodology that practice-based screenwriters can employ to remodel an existing character framework for the writing of a commercially viable anti-heroine teleplay. Historically, we are at a time in which more nuanced and authentic female-based screenplays, which subvert traditional representations of gender, are demanded. To date, anti-heroine characters and publications have been scarce, causing the market to tread carefully due to the perceived financial risk associated. The following methodology proposed offers a robust procedure to revise an existing anti-hero framework into one for the anti-heroine. The author used this methodology for their own practice-based Ph.D. thesis where a major component of the research comprised the development of an anti-heroine teleplay that would be considered for production. The industrial nature of the research aim required the inclusion of traditional research methods prior to practice. For example, the need to conduct textual analysis on case study anti-heroine shows and engage with relevant theory to define an intended audience. Due to the use of some traditional research methods, this could leave the methodology in dispute as practice-based. Before proposing the methodological framework, such concern will be addressed.